Stable Angiogenesis: Mechanically Defined Microenvironment Promotes Stabilization of Microvasculature, Which Correlates with the Enrichment of a Novel Piezo‐1+ Population of Circulating CD11b+/CD115+ Monocytes (Adv. Mater. 21/2019). Issue 21 (21st May 2019) - Forget, Aurelien; Gianni‐Barrera, Roberto; Uccelli, Andrea; Sarem, Melika; Kohler, Esther; Fogli, Barbara; Muraro, Manuele G.; Bichet, Sandrine; Aumann, Konrad; Banfi, Andrea; Shastri, V. Prasad
Abstract : In article number1808050, V. Prasad Shastri and co‐workers describe the formation of a new perfused blood vessel. The stabilization of this neovessel by a mechanically defined hydrogel microenvironment through the recruitment (extravasation) of mechanosensing CD11b + /piezo‐1 + cells by this microenvironment is depicted against the backdrop of a hematoxylin‐eosinstained image of a skeletal muscle.